Salivary Metabolic Pathway Alterations in Brazilian E-Cigarette Users † - Carvalho, Bruna Fernandes do Carmo [UNESP]; Faria, Natalia de Carvalho [UNESP]; Silva, Kethilyn Chris Sousa [UNESP]; Greenfield, Ellen; Alves, Mônica Ghislaine Oliveira [UNESP]; Dias, Meriellen; Mendes, Maria Anita; Pérez-Sayáns, Mario; Almeida, Janete Dias [UNESP] (MDPI, 2024)
In recent years, the use of electronic cigarettes (e-cigs) has increased. However, their long-term effects on oral health and saliva remain poorly understood. Therefore, this study aimed to evaluate the saliva of e-cig users and investigate possible biomarkers. Participants were divided into two groups: the Electronic Cigarette Group (EG)—25 regular and exclusive e-cig users—and Control Group (CG)—25 non-smokers and non-e-cig users, matched in sex and age to the EG. The clinical analysis included the following parameters: age, sex, heart rate, oximetry, capillary blood glucose, carbon monoxide (CO) concentration in exhaled air, and alcohol use disorder identification test (AUDIT). Qualitative and quantitative analyses of saliva included sialometry, viscosity, pH, and cotinine concentrations. Furthermore, the EG and CG salivary metabolomes were compared using gas chromatography coupled with mass spectrometry (GC-MS). Data were analyzed using the Mann–Whitney test. The MetaboAnalyst 6.0 software was used for statistical analysis and biomarker evaluation. The EG showed high means for exhaled CO concentration and AUDIT but lower means for oximetry and salivary viscosity. Furthermore, 10 metabolites (isoleucine, 2-hydroxyglutaric acid, 3-phenyl-lactic acid, linoleic acid, 3-hydroxybutyric acid, 1,6-anhydroglucose, glucuronic acid, valine, stearic acid, and elaidic acid) were abundant in EG but absent in CG. It was concluded that e-cig users had high rates of alcohol consumption and experienced significant impacts on their general health, including increased cotinine and CO concentration in exhaled air, decreased oximetry, and low salivary viscosity. Furthermore, they showed a notable increase in salivary metabolites, especially those related to inflammation, xenobiotic metabolism, and biomass-burning pathways.
Keywords: alcoholic beverages; biomarkers; electronic cigarettes; metabolome; oral health; saliva